2018
DOI: 10.1101/299958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct cortical-amygdala projections drive reward value encoding and retrieval

Abstract: The value of an anticipated rewarding event is crucial information in the decision to engage in its pursuit. The networks responsible for encoding and retrieval this value are largely unknown. Using glutamate biosensors and pharmacological manipulations, we found that basolateral amygdala (BLA) glutamatergic activity tracks and mediates both the encoding and retrieval of the hungerstate-dependent value of a palatable food reward. Projection-specific chemogenetic and optogenetic manipulations revealed and it wa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 113 publications
(151 reference statements)
3
36
0
Order By: Relevance
“…Recent work suggests OFC is critical for incentive learning processes, both at the point of encoding the updated value (Baltz et al, 2018; Malvaez et al, 2019) and when retrieving the updated value from memory to control responding (Malvaez et al, 2019). However, it is currently unknown whether alcohol‐induced deficits in incentive learning are largely driven by changes to OFC function.…”
Section: Alcohol Dependence and The Ofc Cognitive Mapmentioning
confidence: 99%
“…Recent work suggests OFC is critical for incentive learning processes, both at the point of encoding the updated value (Baltz et al, 2018; Malvaez et al, 2019) and when retrieving the updated value from memory to control responding (Malvaez et al, 2019). However, it is currently unknown whether alcohol‐induced deficits in incentive learning are largely driven by changes to OFC function.…”
Section: Alcohol Dependence and The Ofc Cognitive Mapmentioning
confidence: 99%
“…This is consistent with our observation of GIRK channel-independent suppression of spikeevoked Ca 2+ transients after eOPN3 activation. Thus, if locally activated at synaptic terminals, eOPN3 is a robust and broadly applicable optogenetic tool for inhibition of synaptic neurotransmission, similar to the DREADD receptor hM4Di, which has been successfully used for presynaptic silencing in a variety of neuronal cell types and systems (Stachniak, et al, 2014;Evans, et al, 2018;Malvaez, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A hallmark of OFC function is its contribution to reward evaluation and updating, with increases in OFC activity observed during outcome anticipation and presentation (Rolls et al, 1996; Jones et al, 2012; Wallis, 2012; Stalnaker et al, 2014, 2015, 2018). Recent works have shown that inhibition of OFC activity during periods of outcome presentation prevent outcome evaluation and updating (Baltz et al, 2018; Malvaez et al, 2019). Further, recent work in humans has suggested that OFC encodes reward identity expectations (Howard & Kahnt, 2018), which contribute to the generation of prediction errors even when there is no change in value (Stalnaker et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence implicate the OFC as a key contributor to computations that can contribute to value-based decision-making processes (Fellows, 2007; Wallis, 2007; Gremel & Costa, 2013; Stalnaker et al, 2015; Padoa-Schioppa & Conen, 2017) as well as to compulsive control (Milad & Rauch, 2012; Pauls et al, 2014; Robbins et al, 2019; Lüscher et al, 2020). In particular, manipulations of OFC function support a role for OFC in the updating and retrieval of expected outcome value to control behavior (Gremel & Costa, 2013; Rhodes & Murray, 2013; Baltz et al, 2018; Malvaez et al, 2019), as well as in compulsive action control (Ahmari et al, 2013; Burguière et al, 2013; Pascoli et al, 2015, 2018). Animal models of alcohol dependence have revealed long-lasting dependence-induced disruptions to OFC dependent processes including behavioral flexibility and outcome devaluation (Badanich et al, 2011; Kroener et al, 2012; M. F. Lopez et al, 2014; Fernandez et al, 2017; Renteria et al, 2018, 2020).…”
Section: Introductionmentioning
confidence: 97%